Güvenilir Haber Almada Uydudan Uzaktan Algılamanın Kullanımı - Çağlak, Engin; Özelkan, Emre (Muş Alparslan Üniversitesi, 2019)
In journalism, receiving the correct data from a reliable source isessential. In an environment where there is a lack of data, the news items arealso missing. Achieving the right and concrete information and accordinglytaking measures against damages that may arise later and are of greatimportance for journalism. In this context, satellite technology is one of themost reliable tools of gathering information. In this study, in terms ofjournalism, the advantages of satellite remote sensing were explained withexamples from past events and the importance of satellite technology wasinvestigated. The work's universe is sample news lived and published on the weband field studies through satellite images. As a result, the study reveals howsatellite technology can be used accurately and quickly in terms of newsgathering techniques. Additionally, this study emphasized the advantages ofsatellite remote sensing technology against conscious or unconsciousinformation distortions.

Haberciliktedoğru veriyi güvenilir kaynaktan almak esastır. Veri eksikliğinin olduğu birortamda yapılan haberin öğeleri de eksiktir. Kitle iletişim araçlarının, istenmeyen etkilerini önlemek veya doğru bilgiye hızlı ve somut bir şekildeulaşmak gazetecilik açısından büyük önem taşımaktadır. Bu bağlamda uyduteknolojileri bilgi toplamak için en güvenilir araçlardan biridir. Bu çalışmadauydudan uzaktan algılamanın habercilik açısından sağladığı avantajlar geçmişteyaşanan olaylardan örneklerle anlatılmış ve habercilik açısından önemiaraştırılmıştır. Çalışmanın evreni geçmişte yaşanmış ve yayınlamış örnek haberincelemeleri ve uydu görüntüleri üzerinden saha çalışmalarıdır. Bu çalışmanınsonucunda, zamanla yarışan habercilik sektöründe, uydu teknolojilerinin habertoplama teknikleri açısından doğru ve hızlı kullanımının gerekliliği ortayakonmaktadır. Aynı zamanda bilinçli veya bilinçsiz olarak yapılandezenformasyona karşın uydudan uzaktan algılama teknolojisinin önemivurgulanmaktadır.
Using Satellite Remote Sensing in Collecting Reliable News
anemon
Keywords: News; Journalism; Satellite Technologies; Remote Sensing; Reliable News Acquisition; Haber; Haber Toplama; Dezenformasyon; Uydudan Uzaktan Algılama; Gazetecilik